Disperser coupled rhamnolipid disintegration of pulp and paper mill waste biosolid: Characterisation, methane production, energy assessment and cost analysis. (February 2020) - Sethupathy, A.; Arunagiri, A.; Sivashanmugam, P.; Banu, J. Rajesh; Ashokkumar, Muthupandian
Graphical abstract: Highlights: RLD dose (0.009 g/g TS) with pH 10 had a significant effect on PPST sludge. Disperser coupled RLD method got maximal liquefaction rate at 5128 kJ/kg TS. A higher methane production was attained by disperser coupled RLD method. Disperser coupled RLD method was obtained a positive net energy of 900.64 kWh. A net profit of 134 / ton of sludge was achieved by disperser coupled RLD method. Abstract: In this study, the disintegration potential of disperser coupled rhamnolipid (RLD) was investigated on pulp and paper mill secondary sedimentation tank (PPST) sludge. Initially, RLD dosage and pH were optimized for liquefied organic content release. Maximal of liquefied organic content release of 2158 mg/L was attained at an optimized RLD dosage (0.009 g/g TS (Total solids), pH 10). To augment liquefaction of PPST sludge further, disperser and disperser coupled RLD methods were carried out. Disperser coupled RLD method has achieved maximal liquefaction rate (27%) and total suspended solids (TSS) reduction (20%) at 5128 kJ/kg TS when compared to disperser method. Subsequently, methane assay was performed in which disperser coupled RLD method yielded higher methane production of 295 mL/g VS (Volatile solids). Then, cost analysis was performed in which disperser coupled RLD method achieved a net profit of 134 / ton of PPST sludge.